Pelatihan Editing Video Menggunakan CapCut di SMA Plus Nurul Mubin - Ardian Maulana; Lalu Mutawalli (Lembaga Pengembangan Kinerja Dosen, 2025)
The video editing training using the CapCut application at SMA Plus Nurul Mubin aimed to enhance students' digital skills in line with the competency demands of today's creative industry era. The training was conducted through hands-on learning, involving direct practice in various video editing techniques, from basic to advanced levels. Evaluation results showed that participants experienced a significant improvement in video editing skills, although several technical obstacles such as device and application limitations were encountered. In general, the training was considered successful in enhancing creativity, technical abilities, and participants' readiness to produce innovative digital content. These findings support previous studies that emphasize the effectiveness of mobile application-based training in improving the competitiveness of the younger generation in the workforce. Through the optimal use of CapCut, participants are expected to be more adaptive to future developments in digital technology.